Peran Konselor Adiksi Dalam Pemulihan Pecandu Penyalahgunaan Napza (Studi Penelitian Di Yayasan Rumoh Geutanyoe Aceh) - Mai Syarah (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
Drug abuse is increasing day by day, and healing is also done in various ways, one way to recover for victims of drug abuse is through an addiction counselor. In this thesis, we examine the role of addiction counselors in the recovery of drug abuse addicts at the Rumoh Geutanyoe Foundation, Aceh. This type of research is field research with qualitative research methods. This research was carried out by observation and interviews with a number of respondents and informants so that the results were described narratively. The results of this research found that, the role of addiction counselors for the recovery of drug abuse addicts at the Rumoh Geutanyoe Aceh Foundation is by screening to determine the next action to be taken and applying techniques that are appropriate to the resident's needs, after that the counselor places new clients in a special room with the aim of eliminates the effects of the substance without a replacement drug. Then the program starts for 4 months or more depending on the progress assessed in the program by the counselor. Apart from that, counselors also experience obstacles such as addicts who have serious illnesses that require special medical treatment. Apart from that, each resident has different problems and characteristics so counselors need to adapt to face new problems. Based on the results of this interview, it is recommended that addiction counselors for the recovery of drug abuse addicts at the Rumoh Geutanyoe Aceh Foundation be carried out well, namely: Addiction counselors to carry out more training or additional education in maximizing the competency of addiction counselors. Always improve his personal qualities to become a better agent of change for victims of drug abuse.